THE USE OF CONTEXTUAL ANALYSIS IN TEACHING VOCABULARY - Samita, Fitrah; Supardi, Iwan; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to find out the effectiveness of the use of contextual analysis in teaching vocabulary to the tenth grade students of MAN 2 Pontianak in academic year 2013/2014. This research was conducted as a pre experimental research with the one group pretest-posttest. The sample of this research were class X MIA 1 as the experimental class. The data were collected through pretest and posttest by using multiple choice consisting of twenty items and were analyzed by using Effect Size (ES) formula. The finding shows that the effect of treatment is 1.3 (>1.00) or categorized as strong effect. It indicates that the use of contextual analysis is effective in teaching vocabulary. Keywords: Contextual Analysis, vocabulary Abstrak: Penelitian ini bertujuan untuk mengetahui keefektifan penggunaan analisis konteks dalam pengajaran kosa kata terhadap siswa kelas X MAN 2 Pontianak tahun ajaran 203/2014. Penelitian ini dilakukan dengan menggunakan metode pre eksperimen dengan desain pretest dan posttest. Sampel penelitian ini terdiri dari kelas X MIA 1 sebagai kelas eksperimen. Data penelitian dikumpulkan melalui pretest dan posttest dengan menggunakan tes pilihan ganda yang berjumlah dua puluh soal dan data tersebut dianalisa dengan menggunakan rumus ES (Tingkat Efektifitas). Hasil penelitian menunjukan bahwa efek dari penggunaan contextual analysis adalah 1.3 (>1.00) atau dikategorikan memiliki efek yang kuat. Hal ini menandakan bahwa penggunaan contextual analysis efektif dalam pengajaran kosa kata. Kata kunci : Analisis Konteks, Kosa Kata